European Union policy on smokeless tobacco: a statement in favour of evidence based regulation for public health. (5th December 2003) - Bates, C; Fagerström, K; Jarvis, M J; Kunze, M; McNeill, A; Ramström, L
Abstract : Rationale: This statement is an updated version of one released by the same authors in February 2003. The statement was produced to follow up the Royal College of Physicians (RCP) Tobacco Advisory Group report "Protecting smokers, saving lives: the case for a tobacco and nicotine regulatory authority", 1 which argued for an evidence based regulatory approach to smokeless tobacco and harm reduction and posed a series of questions that regulators must address in relation to smokeless tobacco. The purpose of this statement is to provide arguments of fact and principle to follow the RCP's report and to outline the public health case for changing existing European Union (EU) regulation in this area. A review of regulation in relation to harm reduction and regulation of tobacco products other than cigarettes is required in Article 11 of EU directive 2001/37/EC, 2 and this is a contribution towards forming a consensus in the European public health community about what policy the EU should adopt in the light of this review, or following ongoing legal action that may potentially strike out the existing regulation altogether. Public health case: We believe that the partial ban applied to some forms of smokeless tobacco in the EU should be replaced by regulation of the toxicity of all smokeless tobacco. We hold this view for public health reasons: smokeless tobacco is substantially less harmful than smoking and evidence from Sweden suggests it is used as a substitute for smoking and for smoking cessation. To the extent there is a "gateway" it appears not to lead to smoking, but away from it and is an important reason why Sweden has the lowest rates of tobacco related disease in Europe. We think it is wrong to deny other Europeans this option for risk reduction and that the current ban violates rights of smokers to control their own risks. For smokers that are addicted to nicotine and cannot or will not stop, it is important that they can take advantage of much less hazardous forms of nicotine and tobacco—the alternative being to "quit or die"… and many die. While nicotine replacement therapies (NRT) may have a role in harm reduction, tobacco based harm reduction options may reach more smokers and in a different, market based, way. Chewing tobacco is not banned or regulated in the EU but is often highly toxic, and our proposal could remove more products from the market than it permitted. Regulatory options: We believe that the EU policy on smokeless tobacco should adapt to new scientific knowledge and that the European Commission should bring forward proposals to amend or replace Article 8 of directive 2001/37/EC with a new regulatory framework. Canada has developed testing regimens for tobacco constituents and these could be readily adapted to the European situation. A review of EU policy in this area is required no later than December 2004, and we believe the Commission should expedite the part of its review that deals with harm reduction and regulation of tobacco products other than cigarettes so as to reconsider its policy on smokeless tobacco. We held this view before Swedish Match brought its legal proceedings to challenge EU legislation and we will continue to hold these views if its action fails.